Brottsenhet vid koppleri och människohandel - Kallio, Heikki (Nordisk Tidsskrift for Kriminalvidenskab, 2023)
Abstract Before the 2010s, questions regarding conflict of crimes had not gained much attention in the Finnish criminal jurisprudence. However, in more recent years such questions have been increasingly discussed. This is largely attributable to the Supreme Court of Finland having taken a stance on this question several times in the 2000s. The most recent precedent on conflict of crimes was issued by the Supreme Court in the beginning of 2022. In the precedent KKO 2022:2, which concerned human trafficking for the purpose of labour, the Supreme Court took a stance on the counting of criminal offences in the context of human trafficking. It follows from the precedent that weight shall be given to the number of injured parties (crime victims) when determining whether individual acts constitute one or several criminal counts in the context of crimes that strongly violate legal interests linked to a person, such as health, freedom and the right to self-determination. The current paper uses the recent precedent to suggest how counting should be done within the context of other types of human trafficking and closely related crimes, such as procuring. The analysis concludes that when counting criminal offences, one must pay attention to differences between various types of crime, including the legal interests protected by the provision in question. Moreover, the circumstances of the case and the differences in criminal methods will affect the count, thus leading to different results. Criteria developed from case law and jurisprudence are given different weight depending on the applicable penal provisions and the circumstances of the case. It is noteworthy that neither the counting criteria nor the weights applied are permanent, but can vary as a consequence of social change. Social change regarding the position of crime victims has, in fact, affected the counting of criminal offences in the sense that nowadays more weight is given to the number of crime victims.